Subphthalocyaninato Boron(III) Hydride: Synthesis, Structure and Reactivity. Issue 47 (7th July 2021) - Tejerina, Lara; Labella, Jorge; Martínez‐Fernández, Lara; Corral, Inés; Victoria Martínez‐Díaz, M.; Torres, Tomás
Abstract: Subphthalocyanine (SubPc) chemistry has been limited so far by their high sensitivity toward strong nucleophiles. In particular, the substitution of the axial chlorine atom by a nucleophilic group in the case of less‐reactive SubPcs, such as those bearing electron‐withdrawing peripheral substituents, presents some limitations and requires harsh conditions. By taking advantage of the electrophilic character of DIBAL‐H, it has been possible to prepare for the first time SubPc‐hydride derivatives that exhibit high reactivity as hydroboration reagents of aldehydes. This hydride transfer requires using a typical carbonyl activator (trimethylsilyl triflate) and only one equivalent of aldehyde, affording SubPcs with an axial benzyloxy group in good yield. This transformation has proven to be a useful alternative method for the axial functionalisation of dodecafluoroSubPc, a paradigmatic SubPc derivative, by using electrophiles for the first time. Considering the increasing interest in SubPcs as electron‐acceptor semiconductors with remarkable absorption in the visible range to replace fullerene in organic photovoltaic (OPV) devices, it is of the utmost importance to develop new synthetic methodologies for their axial functionalisation. Abstract : For the first time subphthalocyanine‐hydride derivatives that exhibit high reactivity as hydroboration reagents of aldehydes have been prepared. This transformation has proven to be a useful alternative method for the axial functionalisation of dodecafluoro‐subphthalocyanines using electrophiles. Considering the increasing interest in SubPcs as electron‐acceptor semiconductors to replace fullerene in organic photovoltaic devices, it is of the utmost importance to develop new synthetic methodologies for their axial functionalisation.